PENGARUH AKUNTABILITAS, KREDIBILITAS, DAN TRANSPARANSI TERHADAP MINAT MEMBAYAR ZAKAT PADA LEMBAGA AMIL ZAKAT DI SURAKARTA - Angrahita Grahesti; Ayna Sekar Hutami; Jundiyah Mifthahur Rohmah (ITB AAS INDONESIA Surakarta, 2023)
This study aims to determine whether there is an effect of accountability, transparency and credibility on the intention to pay zakat at amil zakat institutions in Surakarta. In this study, researchers used a quantitative approach to the sampling technique, namely random sampling. The results of the study show that partially the accountability and transparency variables do not have a significant effect on the intention to pay zakat at amil zakat institutions in Surakarta. Meanwhile, the credibility variable partially shows an influence on the intention to pay zakat at amil zakat institutions in Surakarta. Based on the simultaneous test, the variables of accountability, transparency, and credibility jointly influence the intention to pay zakat at amil zakat institutions in Surakarta.